Flutter assessment on composite plate with crack by means of fully coupled Finite Element and Doublet Lattice Method - Abdullah, Nur Azam; Curiel-Sosa, Jose Luis; Akbar, Mahesa (2017)
This paper presents an investigation on flutter behaviour of composite plate with crack. This work is divided into two sections; (a) variation of crack length at a fix location on the plate, (b) variation of crack location on the plate with a fix crack length. The composite plate is modelled as unidirectional composite for 0°, 45° and 90° orientation. Mori-Tanaka homogenization model is applied to obtain the effective composite constitutive properties as the function of fiber and matrix volume fraction. Shell elements are implemented to model the plate structure. Doublet Lattice Method (DLM) is used to calculate the unsteady aerodynamic forces. PK-method is applied to obtain the flutter solution. For section (a), the results show that as the length of the crack increased, the damping of the system is decreased, thus the critical flutter speed decreased for all fiber orientation. However, for section (b), the critical flutter speed is found to be increasing as the crack location move from the root of the plate to the tip of the plate, as the aerodynamics load is almost similar to the undamaged plate.